Якої історії потребує сучасна Україна? - Плохій, С.М. (Український історичний журнал, 2013)
Стаття представляє собою роздуми автора над шляхами створення сучасного українського історичного наративу. Поштовхом до її написання став майже одночасний вихід у світ двох видань Павла Роберта Маґочія – англомовної
«Ілюстрованої історії України» (Торонто, 2007 р.) та україномовної «Історії
України» (Київ, 2007 р.). Подано ширший контекст європейського й українського
історієписання впродовж кінця ХІХ – початку ХХІ ст. This article discusses alternative approaches to the construction of Ukrainian historical
narrative. It deals, among other texts, with two recent works by Paul Robert
Magocsi, the "History of Ukraine", which appeared in Ukrainian translation in Kyiv
in 2007, and "Ukraine: An Illustrated History" (Toronto, 2007). These and other works
of contemporary authors are discussed within a broad context of Ukrainian, European
and North American historiography of the long twentieth century.